Actinopolyspora salinaria sp. nov., a halophilic actinomycete isolated from solar saltern soil - Kannika Duangmal (2018)
© 2016 IUMS. The taxonomic position of the halophilic actinobacterial strain, HS05-03T, isolated from solar saltern soil, was determined using a polyphasic approach. Phylogenetic analysis based on the 16S rRNA gene sequence of the strain showed that it formed a distinct evolutionary lineage in the genus Actinopolyspora. The organism was most closely related to the type strains of the species Actinopolyspora xinjiangensis (98.0 % similarity), Actinopolyspora righensis (97.9 % similarity), Actinopolyspora lacussalsi (97.9 % similarity) and Actinopolyspora erythraea (97.8 % similarity). The whole-organism hydrolysates contained meso-diaminopimelic acid, arabinose, galactose and ribose. The predominant menaquinones were found to be MK-9(H4) and MK-10(H4). The acyl type of the peptidoglycan was N-acetyl. The diagnostic phospholipid detected was phosphatidylcholine. The predominant cellular fatty acids were iso-C16: 0, anteiso-C17: 0 and iso-C15: 0. The G+C content of the genomic DNA was 69.9 mol%. DNA-DNA hybridization values between strain HS05-03T and the type strains of the most closely related species were below the 70 % threshold. On the basis of the phenotypic and genotypic data, it is proposed that strain HS05-03Trepresents a novel species of the genus Actinopolyspora, with the name Actinopolyspora salinaria sp. nov. The type strain is HS05-03T(=BCC 51286T=NBRC 109078T).